Pre-caesarean Anxiety Level in Obstetric Patients Undergoing Elective or Emergency Cesarean Section: A Comparative Study (Bangladesh Journal of Obstetrics & Gynaecology, 2023)
Introduction: A prevalent physiological reaction to stress is the manifestation of anxiety symptoms observed in individuals undergoing surgical procedures. Obstetric patients have been found to exhibit a higher degree of preoperative anxiety in comparison to the general surgical patients. The primary objective of this study was to evaluate and compare the levels of preoperative anxiety among obstetric patients who were scheduled for elective or emergency cesarean section.Methodology: The present study was a cross-sectional comparative study undertaken at the Combined Military Hospital of Bogura, specifically within the Department of Obstetrics and Gynaecology, for one year, from January 2022 to December 2022. According to the American Society of Anesthesiologists, the study included a sample size of 200 obstetric patients classified as physical status II. These patients underwent either elective cesarean section (n=100) or emergency cesarean section. The study employed the Hospital Anxiety and Depression Scale (HADS) and the Visual Analogue Scale for Anxiety (VAS-A) as assessment tools. The study used a purposive sampling strategyResult: In this study, 50% of subjects belonged to the 25 years age group. Most patients, 120 (60%), lived in the urban area, and the rest, 80 (40%) lived in the village. Regarding economic and clinical characteristics, 50% of patients had no personal income, most of the patients (65%) were multigravida, 80% of patients had no chronic illness, 70% had no anesthetic exposure, 85% had no awareness about anesthesia, 60% had awareness about surgery, 50% had the urgency of emergency surgery and 50% had elective surgery. Concerning the factors of anxiety, 90% of patients had postoperative pain, 85% had a fear of being unable to recover, 80% of patients had a fear of complications, and 80% had unexpected results of the operation. Among the patients, 136(68.0%) had precaesarean anxiety when undergoing emergency caesarean surgery while 64 (32.0%) patients had pre-caesarean anxiety when undergoing elective surgery (p